Nutrition-Aware Family Behavior, Feeding And Household-Level Food Security With The Incidence Of Stunting In The Kamaipura Health Center Working Area Sigi Regency - Mellyani, Jhein; Ni Ketut Kariani; Masfufah, Masfufah (Sean Institute, 2024)
WHO and UNICEF estimate that the world's stunting rate is 22.3% of children under five years old globally in 2022, the prevalence of stunting in Indonesia in 2023 is 21.5% and 27.2% in Central Sulawesi. Sigi Regency has a stunting prevalence of 26.4%, Kamaipura Health Center ranks the first highest stunting in October 2023, namely 66% experiencing stunting. The purpose of this study was to analyze the relationship between nutrition-aware family behavior, complementary feeding and food security and analyze the influence of independent variables on the incidence of stunting. This study used a case control design. The population in this study were toddlers aged 24-59 months, the number of samples was 38 case groups and 38 control groups. Based on the results of bivariate analysis using the chi-square test, namely nutrition-aware family behavior, complementary feeding, and food security <0.05, which shows there is a relationship with the incidence of stunting. The results of multivariate analysis using the logistic regression test are that there are no variables that contribute most to the incidence of stunting. However, based on the results of the OR calculation <1, which means that the three variables are protective factors for the incidence of stunting. There is a significant relationship between nutrition-conscious family behavior, complementary feeding and food security with the incidence of stunting, there is no variable that contributes most to the incidence of stunting because all variables are protective factors.For health workers at Kamipura Health Center to be more active in providing education related to nutrition-conscious family behavior, complementary feeding and food security to mothers of toddlers and further researchers to further examine these three variables and other variables.